Constraints of Developing Country Partnership (KNB) Foreign Learners in BIPA Learning Interaction - Eva Ardiana Indrariani; Aziizatul Khusniyah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This research departs from the problem of low active participation of foreign learners in the interaction of Indonesian learning for Foreign Speakers (BIPA), especially those who are members of the Developing Countries Partnership (KNB) program. The verbal constraints they experience are not solely related to language skills, but also closely related to sociocultural, psychological, and pedagogical factors that affect their comfort in classroom interactions. This study aims to identify and describe the interaction obstacles faced by KNB foreign learners in BIPA learning and the factors that affect them as a whole. This study uses a descriptive qualitative approach with data collection techniques such as participatory observation, in-depth interviews, and document analysis. The research subjects consist of international students receiving KNB scholarships and participating in the BIPA program at one of the public universities in Indonesia. The data were analyzed thematically, emphasizing interaction patterns, verbal responses, and adaptation strategies used by learners in the learning context. The results show that the main obstacles in learning interactions come not only from the limitations of vocabulary and sentence structure, but also from the fear of making mistakes, lack of understanding of local communication norms, and lack of pedagogical support that is responsive to the learner's cultural background. These findings confirm the importance of developing BIPA learning strategies that are more inclusive, interactive, and based on intercultural awareness. This research provides theoretical and practical contributions to the development of BIPA teaching and opens up space for further studies in the realm of cross-cultural interaction in language education.